Analysis of the Potential Hazards of Work Accidents Department of Production Using Failure Mode Effect Analysis (FMEA) and Fault Tree Analysis (FTA) Methods in PT. XYZ - Mayasi, Sinyi Retno; Rusindiyanto, Rusindiyanto (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT. XYZ is a company engaged in the business of white crystal sugar with raw sugar cane in Jombang. As the industrial world develops, companies are required to produce products both in terms of quality and quantity. Therefore, the production process has the potential to experience work accidents. To minimize this from happening, this research identified the potential hazards of work accidents in the production division. The methods used are the Failure Mode Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods. Using the FMEA method produced 3 potential hazards with the highest RPN values namely potential for exposed hot ashes at the boiler station with an RPN of 33,716. In second place is the potential collapse of the crane at the mill station with RPN 27,192. Then in third place is the potential Explosion of pipes and tanks at the evaporation station with an RPN value of 23.549. With the FTA method, the 3 potential hazards that have been obtained are used as top events and an analysis is carried out to find out the root causes of the potential accidents that occur. The analysis is grouped from human, equipment, and environmental aspects. From the human factor, it is known that the cause was workers who were not concentrating, were negligent, and did not comply with SOPs. The equipment factor comes from the age of the old tool and lack of maintenance. As well as environmental factors, namely high temperature pressure and humidity which can have an impact on corrosion of iron equipment. So that the suggestions that can be given to companies are imposing sanctions on employees who do not comply with the rules, providing job training according to their respective fields, and scheduling regular machine maintenance.